A wireless sensor network for drip irrigation control and automation - Castro C., Nesly Diana; Chamorro F., Luis Eduardo; Viteri M., Carlos Andrés (Revista de Ciencias Agrícolas, 2016)
One of the main objectives of precision agriculture is the crops irrigation according to the particular needs of a cropland. This paper describes the design and implementation of a wireless sensor network, which is able to get soil moisture measurements from different zones of a strawberries crop. A control system determines the irrigation time and the particular zone that must be watered by the drip irrigation method, according to the data collected by the network. Water requirements for crops were estimated by field capacity and irrigation threshold; both parameters were calculated for the entire crop in the production stage. The communication between network nodes is based on the ZigBee protocol stack, and the final prototype is a closed–loop on/off control system with a hysteresis band. Finally, the results showed a more water use efficiency and improved strawberry quality when compared to the traditional irrigation system.